Decoupling the Graphene Buffer Layer SiC(0001) via Interface Oxidation - Ostler, Markus; Koch, Roland; Speck, Florian; Fromm, Felix; Vita, Hendrik; Hundhausen, Martin; Horn, Karsten; Seyller, Thomas (Materials Science Forum, 2012)
Epitaxial graphene (EG) grown on SiC(0001) resides on the so-called buffer layer. This carbon rich (6√3×6√3)R30® reconstruction is covalently bound to the topmost silicon atoms of the SiC. Decoupling the graphene buffer layer from the SiC interface is a well studied topic since successful intercalation has been shown for hydrogen [1-3]. Recently, intercalation was also shown for oxygen [4, 5]. We present angle-resolved photoemission spectroscopy (ARPES), x-ray induced photoelectron spectroscopy (XPS) and Raman spectroscopy studies to determine the quality of oxygen intercalated buffer layer samples in terms of decoupling and integrity of the transformed graphene layer. The decoupling effect is demonstrated by ARPES measurements showing a graphene-like π band. XPS shows whether the oxidation takes place in the buffer layer or at the interface. Raman spectroscopy is well suited to investigate oxygen induced defects in graphene-like material. © (2012) Trans Tech Publications.
UnivIS-Import:2015-03-09:Pub.2012.nat.dphy.IAP.exphys.decoup
Keywords: ARPES; Graphene; Intercalation; Oxidation; Raman spectroscopy; Si-face; XPS

Growth and electronic structure of boron-doped graphene - Gebhardt, Julian; Koch, Roland; Zhao, Wei; Höfert, Oliver; Gotterbarm, Karin; Mammadov, Samir; Papp, Christian; Görling, Andreas; Steinrück, Hans-Peter; Seyller, Thomas (Physical Review B, 2013)
The doping of graphene to tune its electronic properties is essential for its further use in carbon-based electronics. Adapting strategies from classical silicon-based semiconductor technology, we use the incorporation of heteroatoms in the 2D graphene network as a straightforward way to achieve this goal. Here, we report on the synthesis of boron-doped graphene on Ni(111) in a chemical vapor deposition process of triethylborane on the one hand and by segregation of boron from the bulk of the substrate crystal on the other hand. The chemical environment of boron was determined by x-ray photoelectron spectroscopy, and angle-resolved photoelectron spectroscopy was used to analyze the impact on the band structure. Doping with boron leads to a shift of the graphene bands to lower binding energies. The shift depends on the doping concentration and for a doping level of 0.3 ML a shift of up to 1.2 eV is observed. The experimental results are in agreement with density-functional calculations. Furthermore, our calculations suggest that doping with boron leads to graphene preferentially adsorbed in the top-fcc geometry, since the boron atoms in the graphene lattice are then adsorbed at substrate fcc-hollow sites. The smaller distance of boron atoms incorporated into graphene compared to graphene carbon atoms leads to a bending of the doped graphene sheet in the vicinity of the boron atoms. By comparing calculations of doped and undoped graphene on Ni(111), as well as the respective freestanding cases, we are able to distinguish between the effects that doping and adsorption have on the band structure of graphene. Both doping and bonding to the surface result in opposing shifts on the graphene bands. © 2013 American Physical Society.

Growth and electronic structure of nitrogen-doped graphene on Ni(111) - Koch, Roland; Weser, M.; Zhao, Wei; Vines, Francesc; Gotterbarm, Karin; Kozlov, Sergey M.; Höfert, Oliver; Ostler, Markus; Papp, Christian; Gebhardt, Julian; Steinrück, Hans-Peter; Görling, Andreas; et al. (Physical Review B, 2012)
We report on experimental and theoretical investigations of nitrogen-doped graphene. The incorporation of nitrogen was achieved during chemical-vapor deposition on Ni(111) using pyridine as a precursor. The obtained graphene layers were investigated using photoelectron spectroscopy. By studying C 1s and N 1s core levels, we show that the nitrogen content is influenced by the growth temperature and determine the atomic arrangement of the nitrogen atoms. Valence-band photoelectron spectra show that the incorporation of nitrogen leads to a broadening of the photoemission lines and a shift of the π band. Density functional calculations for two possible geometric arrangements, the substitution of carbon atoms by nitrogen and vacancies in the graphene sheet with pyridinic nitrogen at the edges, reveal that the two arrangements have opposite effects on the band structure. For the present experimental approach, vacancies with pyridinic nitrogen are dominant. In the latter case the vacancies generated by the nitrogen doping, not the nitrogen itself, have the main effect on the band structure. By intercalating gold between the doped graphene layer and the Ni(111) substrate electronic decoupling is achieved. After intercalation the doping remains. © 2012 American Physical Society.